Case Report: Dual impact of daratumumab in early T-cell precursor acute lymphoblastic leukemia -- consolidation therapy achieves remission and eliminates donor-specific HLA antibodies - Wong, Kye Ling; Tuy, Tertius; Quek, Jeffrey; Linn, Yeh Ching (Frontiers in Immunology, 2026)
Desensitization of antibodies against human leucocyte antigen (HLA) is an important step in allogeneic hematopoietic stem cell transplantation with mismatched or haploidentical donors. Various strategies have been established to reduce donor specific HLA antibody (DSA) and reduce risk of graft failure. These strategies target a few pathways including depleting B cells, altering plasma cells, removing as well as modifying antibodies. We present a case whereby use of the anti-CD38 monoclonal antibody daratumumab was able to successfully reduce DSA via its action of the cell surface glycoprotein highly expressed on plasma cells in a multiparous patient with early T-cell precursor acute lymphoblastic leukemia (ETP-ALL). In this case, use of daratumumab was originally intended for consolidation therapy of ETP-ALL as treatment related complications encountered during induction therapy precluded use of further systemic chemotherapy. Choice of the anti-CD38 monoclonal antibody was supported by pre-clinical studies suggesting that CD38 is robustly expressed in T-ALL blasts thereby making it a potential effective target for daratumumab. It was through the inadvertent use of this novel agent for ETP-ALL consolidation therapy that a coinciding benefit of reduction in DSA was also achieved. In summary, daratumumab can be considered as a second line or salvage option for desensitization of DSA prior to haploidentical stem cell transplantation especially in multiparous ethnic-minority patients whom we often grapple with the issues of lack of donor availability and multiple DSA.